Transformation of human capital among beneficaries of Program Keluarga Harapan (PKH) in Eastern Java - Anisah, Ajeng Mega; Nurhadi, Nurhadi; Yuhastina, Yuhastina (Harmoni Sosial: Jurnal Pendidikan IPS, 2021)
This research aimed to examine human capital change in beneficiary families of the Family Hope Program (PKH) in Sine, Ngawi. The type of research is quantitative and qualitative research. The data collection technique used primary quantitative data from distributing questionnaires to 67 respondents from a total population of 80 participants and analyzed descriptively. The secondary qualitative data from in-depth interviews with five informants used purposive techniques. The participants' criteria are a mother of at least two years as a PKH participant and a toddler or school-age child. The data analysis technique used data collection, condensation, data presentation, and conclusion. The results showed changes in the human capital of PKH participants in the education or knowledge aspect, namely increasing knowledge about the family and awareness of the importance of education. The health aspect is increasing awareness of clean living. The skill aspect is the addition of new skills in raising livestock and an increase in workability.